2021
DOI: 10.1038/s41477-021-00943-9
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast and mitochondrial DNA editing in plants

Abstract: Plant organelles including mitochondria and chloroplasts contain their own genomes, which encode many genes essential for respiration and photosynthesis, respectively. Gene editing in plant organelles, an unmet need for plant genetics and biotechnology, has been hampered by the lack of appropriate tools for targeting DNA in these organelles. In this study, we developed a Golden Gate cloning system1, composed of 16 expression plasmids (8 for the delivery of the resulting protein to mitochondria and the other 8 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 22 publications
(14 reference statements)
0
77
0
Order By: Relevance
“…The stable inheritance of mitoTALEN‐mediated mitochondrial genome reorganization in null segregants paves the way to mitochondrial genome breeding. A recently developed tool for mitochondrial base editing, mitoTALECD, in which the mitoTALEN nuclease is replaced with a cytidine deaminase (Mok et al., 2020; Kang et al., 2021), would also be effective for use in mitochondrial genome breeding.…”
Section: Discussionmentioning
confidence: 99%
“…The stable inheritance of mitoTALEN‐mediated mitochondrial genome reorganization in null segregants paves the way to mitochondrial genome breeding. A recently developed tool for mitochondrial base editing, mitoTALECD, in which the mitoTALEN nuclease is replaced with a cytidine deaminase (Mok et al., 2020; Kang et al., 2021), would also be effective for use in mitochondrial genome breeding.…”
Section: Discussionmentioning
confidence: 99%
“…To allow for their use in the modification of the mitochondrial and chloroplast genomes, sequence-specific nucleases were redesigned by adding a targeting peptide such as a mitochondrial targeting sequence (MTS) or chloroplast transit peptide (CTP) specific to each organelle. Most recently, Kang et al (2021) reported TALEN plasmids based on bacterial cytidine deaminase (CD) rather than FokI or TevI for mtDNA/cpDNA editing. They generated double-stranded DNA deaminase (DddA) toxin A-derived cytosine base editor (DdCBE) plasmids targeting mtDNA (mt-DdCBE) and cpDNA (cp-DdCBE) via fusion of MTS and CTP, resulting in the efficient introduction of point mutations in the relevant organellar genome, up to 25% in mitochondria and 38% in chloroplast, by mt-DdCBEs and cp-DdCBEs in lettuce ( Lactuca sativa ) and rapeseed, respectively.…”
Section: Editing Of Plant Organellar Genomesmentioning
confidence: 99%
“… 40 , 41 Also, genome editing could be used to induce point mutation in the 16S rRNA gene in the chloroplast genome to enhance antibiotic resistance. 42 , 43 …”
Section: Evolution Of Crispr-cas Systemsmentioning
confidence: 99%